Patchy Forsterite Clouds in the Atmospheres of Two Highly Variable Exoplanet Analogs - Johanna M. Vos; Ben Burningham; Jacqueline K. Faherty; Sherelyn Alejandro; Eileen Gonzales; Emily Calamari; Daniella Bardalez Gagliuffi; Channon Visscher; Xianyu Tan; Caroline V. Morley; Mark Marley; Marina E. Gemma; et al. (The Astrophysical Journal, 2023)
We present an atmospheric retrieval analysis of a pair of highly variable, ∼200 Myr old, early T type planetary-mass exoplanet analogs SIMP J01365662+0933473 and 2MASS J21392676+0220226 using the Brewster retrieval framework. Our analysis, which makes use of archival 1–15 μ m spectra, finds almost identical atmospheres for both objects. For both targets, we find that the data is best described by a patchy, high-altitude forsterite (Mg _2 SiO _4 ) cloud above a deeper, optically thick iron (Fe) cloud. Our model constrains the cloud properties well, including the cloud locations and cloud particle sizes. We find that the patchy forsterite slab cloud inferred from our retrieval may be responsible for the spectral behavior of the observed variability. Our retrieved cloud structure is consistent with the atmospheric structure previously inferred from spectroscopic variability measurements, but clarifies this picture significantly. We find consistent C/O ratios for both objects, which supports their formation within the same molecular cloud in the Carina-Near moving group. Finally, we note some differences in the constrained abundances of H _2 O and CO, which may be caused by data quality and/or astrophysical processes such as auroral activity and their differing rotation rates. The results presented in this work provide a promising preview of the detail with which we will characterize extrasolar atmospheres with JWST, which will yield higher-quality spectra across a wider wavelength range.